Otosclerosis under microCT: New insights into the disease and its anatomy - O'Toole Bom Braga, Gabriela; Zboray, Robert; Parrilli, Annapaola; Bulatović, Milica; Caversaccio, Marco Domenico; Wagner, Franca (Frontiers in Radiology, 2022)
Otospongiotic plaques can be seen on conventional CT as focal lesions around the cochlea. However, the resolution remains insufficient to enable evaluation of intracochlear damage. MicroCT technology provides resolution at the single micron level, offering an exceptional amplified view of the otosclerotic cochlea. A radiological and a 3D anatomical study of an otosclerotic cochlea using microCT technology is presented here for the first time. Three-dimensional segmentation of the human cochlea was performed, providing an unprecedented view of the diseased area without the need for decalcification, sectioning, or staining. Using microCT at single micron resolution and geometric reconstructions, it was possible to visualize the disease’s effects. These included intensive tissue remodeling and highly vascularized areas with dilated capillaries around the spongiotic foci seen on the pericochlear bone. The cochlea’s architecture as a morphological correlate of the otosclerosis was also seen. With a sagittal cut of the 3D mesh, it was possible to visualize intense ossification of the cochlear apex, as well as the internal auditory canal, the modiolus, the spiral ligament, and a large cochleolith over the osseous spiral lamina. Additionally, the oval and round windows showed intense fibrotic tissue formation and spongiotic bone with increased vascularization. Given the recently described importance of the osseous spiral lamina in hearing mechanics and that, clinically, one of the signs of otosclerosis is the Carhart notch observed on the audiogram, a tonotopic map using the osseous spiral lamina as region of interest is presented. An additional quantitative study of the porosity and width of the osseous spiral lamina is reported.